Managing anxiety in eating disorders with knitting. - Clave-Brule, M; Mazloum, A; Park, R; Harbottle, E; Birmingham, C (2009)
OBJECTIVE: Recovery from anorexia nervosa (AN) is often confounded by intrusive, anxious preoccupations with control of eating, weight and shape. These are distressing and represent a potential barrier to psychological change. Theoretical and empirical evidence suggests that performing a concurrent visuospatial task reduces the emotional intensity of distressing images. We assessed whether the visuospatial task of knitting influences the anxious preoccupation experienced by inpatients with AN. METHOD: Prospective interventional cohort. SUBJECTS: Thirty-eight women with AN admitted to a specialized eating disorder unit. INTERVENTION: All subjects were given knitting lessons and free access to supplies. MEASURE: Subjects were asked to report the qualitative effects of knitting on their psychological state using a self-report questionnaire. RESULTS: Patients reported a subjective reduction in anxious preoccupation when knitting. In particular, 28/38 (74%) reported it lessened the intensity of their fears and thoughts and cleared their minds of eating disorder preoccupations, 28/38 (74%) reported it had a calming and therapeutic effect and 20/38 (53%) reported it provided satisfaction, pride and a sense of accomplishment. DISCUSSION: This preliminary data suggests that knitting may benefit inpatients with eating disorders by reducing their anxious preoccupations about eating, weight and shape control. The specificity of this effect is yet to be determined. This preliminary outcome requires further controlled study in AN subjects. From a clinical perspective, knitting is inexpensive, easily learned, can continue during social interaction, and can provide a sense of accomplishment. The theoretical and empirical rationale for this observation, and implications for deriving alternative strategies to augment treatment in AN, are discussed.